THE TRANSFORMATION OF IMKAN AL-RU’YAH (CRESCENT VISIBILITY) CRITERIA IN MALAYSIA: CHALLENGES AND SOLUTIONS (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
This paper examines the Imkan al-Ru’yah method used in Malaysia to determine the visibility of the crescent moon at sunset, marking the beginning of the Hijri month. It explores the criteria for identifying the new moon, the challenges associated with its application, and potential solutions. Through an analysis of crescent sighting practices and local issues, the study highlights the complexities of the method. A review of existing literature evaluates the validity and adaptability of the latest criteria in light of advancing astronomical knowledge. Notably, the study identifies the role of social media in disseminating critical astronomical information to the Malaysian public. This finding underscores the need to integrate traditional methodologies with modern technology to enhance accuracy and accessibility in Hijri calendar determination. Ultimately, the paper emphasizes the evolving nature of astronomical methods and advocates for a balanced approach that harmonizes scientific advancements with established traditions.